The impact of work group diversity on performance: Large sample evidence from the mutual fund industry - Michaela Bär; Alexandra Niessen; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2007)
This paper investigates the impact of work group diversity on performance. Analyzing a uniquely large sample of management teams from the U.S. mutual fund industry we find that the influence of diversity on performance depends on the dimension of diversity that is analyzed. Informational diversity has a positive impact on performance, which is driven by tenure diversity as well as educational diversity. Social category diversity has a negative impact on performance, which is mainly driven by gender diversity while age diversity has no strong impact. Our results have important implications for the optimal composition of work groups and for investment strategies of fund investors.
Keywords: G23; J21; L22; 330; Diversity; Teams; Gender; Mutual Funds; Performance